The Effects of UV Exposure on the Antioxidant Enzyme Systems of Anemones - CAPARKAYA, D.; CENGIZ, S.; DINCEL, B.; DEMIR, S.; CAVAS, L. (Mediterranean Marine Science, 2010)
Superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) which are housekeeping enzymes protect cells from harmful side effects of reactive oxygen species (ROS). Anemonia sulcata var. smaragdina andAnemonia rustica are widely distributed along the Turkish coastlines of Aegean Sea. Recent studies showed that the environmental stresses such as elevated temperature, ultraviolet light, pathogen infection and decreased salinity might cause well known bleaching effects in Anemonia species. The effect of UV-light on antioxidant enzyme activities such as SOD, CAT, GSH-Px, protein levels and secondary pigments were determined in A. sulcata var. smaragdina and A. rustica. SOD, CAT, GSH-Px activities, protein levels and secondary pigments of these morphotypes were observed in both tentacles and columns separately. According to studies on bleaching, the elevated UV radiation may cause this bleaching event as a stress factor. However, in the present study no bleaching event was observed in anemone samples even they are exposed to 5 hours UV-exposure. Moreover, UV exposure did not change antioxidant systems remarkably. However, many investigations are still needed for obtaining the complete picture of the effects of UV-light on cellular pathways of cnidarian–algal symbiosis.